Given: F(x) = 3×2+ 1, G(x) = 2x – 3, H(x) = x F(3) + G(4) – 2H(5) =

Question

Given: F(x) = 3×2+ 1, G(x) = 2x – 3, H(x) = x

F(3) + G(4) – 2H(5) =

in progress 0
Gerda 2 months 2021-07-30T02:09:39+00:00 2 Answers 3 views 0

Answers ( )

    0
    2021-07-30T02:11:21+00:00

    Answer:

    These are functions, you must operate accordingly

    Step-by-step explanation:

    0
    2021-07-30T02:11:24+00:00

    is the 2 in 3×2 an exponent

    if it is the answer is 81

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )